Tratamiento odontológico multidisciplinario de un paciente complejo con fisura labiopalatina bilateral - Leiva Villagra, Noemí (2017)
The cleft lip and palate is the most common congenital malformation between head and neck anomalies. It has an impact on the quality of life of the patient and his family, therefore a multidisciplinary and timely management of its sequels is fundamental for his development. The purpose of this clinical case was to show the integral dental management of a patient diagnosed with bilateral cleft lip and palate, female, 14 years old, who went with her mother to the Institute of Craniofacial Malformations of the University of Chile because they wanted a solution for her altered facial aesthetics and correction of dental malposition. Through the multidisciplinary management it was expected to achieve an adequate functioning of the stomatognathic system and to correct the esthetics for which it was subjected to an orthodontic, surgical and rehabilitating treatment. After this, positive results were obtained in terms of a functional occlusion and a satisfactory dental and facial aesthetic. In conclusion, multidisciplinary management presents a challenge to a dentist from the moment in which he desires to obtain satisfactory results by offering a wider approach of the treatment alternatives for his patients. This does not imply to choose an ideal treatment but rather the best functional and aesthetic alternative; hence the patient can choose the right one, according to their means and expectations.